ANALISIS PENGARUH HUNIAN KAMAR TERHADAP PENJUALAN PADA OUTLET LAYANAN DI HOTEL RAHARDJO BARU KOTA MADIUN - Eko Argo Adi Saputro; Juli Murwani; Yulin Suswandari (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
Purpose of execution of the research is to better know and understand:  1) The room occupancy rate in hotel Raharjo Madiun, 2) to determine the level of sales at the laundry service outlet in hotel Raharjo Madiun, 3) to determine the level of sales service outlet stores / retail in hotel Raharjo Madiun, 4) to determine the effect of room occupancy on sale at outlets laundry services, and 5) to determine the effect of room occupancy on sale at outlet store service / retail. The subjects were drawn from the sales outlet service data and room occupancy during 2011 at hotels Raharjo Baru Madiun. The research is a case study research method used is descriptive qualitative method to assess the influence of occupancy and a quantitative analysis to determine the effect. Test data analysis using simple regression analysis and product moment correlation technique. Data collection techniques are the observation and documentation. From the analysis it can be concluded that: 1) Hotel Rahardjo Baru Madiun is economic class hotel at Madiun that have city category, 2). Hotel New Rahardjo Madiun have a low level laundry service, 3). Hotel Rahardjo Baru Madiun have a high level of retail services with the best quality and are influenced by the high quality of services to consumers, 4). Regression equations:  Y1 = 5.54 + 0.04 X. Then Freg values obtained at 1.5 <from Ft. (4.96). Product moment correlation coefficient through r0 yield 0.372. T test results indicate that the resulting tcount of 1.27 is greater than ttabel at the 5% significance level (α = 0.05) obtained 0.576 TTable. Because tcount greater than ttable then Ho is rejected and Ha accepted. It can be concluded that there is significant room occupancy effect on sales outlets laundry service although the degree of relationship between variables is low, and 5) Regression equation: 102.75 + Y2 = 0.142 X. Then Freg values obtained for 0.514 <from Ft. (4.96). Product moment correlation coefficient through r0 yield 0.224. T test results indicate that tcount is generated by 3.16 greater than ttabel at the 5% significance level (α = 0.05) obtained 0.576 TTable. Since tcount greater than ttable then Ho is rejected and Ha accepted. It was therefore concluded that there is significant room occupancy influence on retail sales outlets service in the hotel Rahardjo Baru Madiun although the degree of correlation between variable is low.